Drew Binsky’s Journey Through The Muslim World: Transforming Global Perceptions of Islam Through People-To-People Diplomacy - Hasbi Aswar; Nazila Alfayed; Auliya Eka Safitri; Silvia Jultikasari Febrian (Afkaruna: Indonesian Interdisciplinary Journal of Islamic Studies, 2024)
This study explores Drew Binsky's journey in the Muslim world and how it has the potential to influence global perceptions of Islam positively. Drew Binsky is a renowned travel vlogger who has explored various countries, delving into their cultures, traditions, and daily lives. Drew Binsky has engaged with Muslim communities in different countries throughout his journeys, sharing these experiences through vlogs and social media platforms. Despite being Jewish and born in the United States, his perception of Islam and Muslims has transformed after visiting and interacting with Muslim communities. Uploaded and shared on social media platforms, particularly YouTube, these experiences contribute to offering an alternative perspective on Islam to the global audience, challenging long-standing misconceptions perpetuated by mainstream global media, scholars, and Islamophobic politicians. The study employed the People-to-People Diplomacy approach to discuss Binsky's efforts through the videos uploaded on his YouTube channel. Research findings indicate that despite being an American Jew, Binsky holds a positive view of Islam and has shared his perspective through videos watched by millions, appreciated not only by Muslim viewers but also by non-Muslim audiences.